Untranslatable flavours: examining the loss of culinary and cultural nuance in Chinese-to-English dish name translation - Lay, Shi Ng; Ruey, Shing Soo; Chun, Keat Yeap (Penerbit Universiti Kebangsaan Malaysia, 2025)
As globalisation broadens culinary exposure, accurately translating Chinese food names into English has become crucial in bridging cultural and linguistic gaps for international diners. However, the translation of Chinese dish names into English often entails a significant loss of culinary and cultural nuance, resulting in a diminished representation of the original flavours, techniques, and heritage. This study explores the intricacies and limitations inherent in conveying the essence of Chinese cuisine to English-speaking audiences. The research aims to investigate the extent to which translation fails to capture essential cultural and culinary elements, thereby impacting international diners' understanding and appreciation of Chinese dishes. The primary objectives of this research are to explore how translation strategies such as literal translation, transliteration, and term translation affect the conveyance of culinary and cultural elements, and to evaluate the extent of nuance loss in translation. Methodologically, a corpus of English-translated Chinese dish names was compiled and analysed to examine the linguistic structures, cultural markers, and culinary terms to uncover patterns and identify translation limitations. This study adopts Cultural Translation Theory as its analytical framework to examine how cultural meanings are mediated and transformed across languages, with a focus on the interplay between language, culture, and identity in the context of culinary discourse. The analysis drew on established frameworks in translation studies and cultural semiotics to interpret how language choices influence the perception of the original dishes. By focusing exclusively on comparative analysis, this study provides insights into the complexities of culinary translation, highlighting the challenges of preserving cultural authenticity in cross-linguistic contexts. The study reveals that the translation of Chinese dish names into English is shaped less by cultural fidelity than by pragmatic considerations of clarity, accessibility, and marketability.